Розробка методики розрахунку поздовжньо-кутових коливань транспортних засобів за нелінійних характеристик підвіски - Сокіл, Марія; Чаган, Юрій (Видавництво Львівської політехніки, 2011)
Використовуючи асимптотичні методи нелінійної механіки у поєднанні із періодичними Ateb-функціями побудовано перше наближення розв'язку системи диференціальних рівнянь, яка є математичною моделлю поздовжньо-кутових коливань транспортних засобів. Отримані так звані рівняння у стандартному вигляді визначають вплив геометричних та динамічних параметрів підвіски на поздовжньо-кутові коливання транспортних засобів. Caterpillar vehicles are maintained in more difficult conditions, than wheel. It puts more rigid requirements to characteristics and layout of their suspension. It should ensure necessary smoothness of a course of a vehicle and the limited dynamic loads at significant speeds of motion on a cross-country terrain. Such requirements are ensured with the suspension with nonlinear communication between moving and restoring force. Simultaneously with nonlinearity of the elastic characteristic of the suspension there are significant difficulties of analytical research of dynamics of a probed vehicle. In work, for sedate or close to it of the communication law between restoring force and moving, the mathematical model of longitudinalangular oscillations is constructed. The technique of construction of the analytical solution of system of the nonlinear differential equations which describes dynamic process of a vehicle is developed for the analysis of effect of main specifications on dynamics of the process. The technique is based on the usage of periodic Atebfunctions at construction of the asymptotic solution of the indicated equations. It allows to receive ratio convenient for the analysis that laws of change of main specifications of vertical and longitudinal-angular oscillations describe. The settlement relations received on the basis of analytical investigations show: – To ensure necessary comfortableness of probed vehicles the suspension with communication between force and deformation in the form of the sedate law provided that a parametre of nonlinearity more than 1 can; – As to characteristics of dampers the necessary vibration damping ensures the nonlinear law of velocity function with a parametre of nonlinearity more from 2. The developed technique in the following can be the basis for research of more difficult and important case - researches of forced oscillations.
Development of a design procedure of longitudinal-angular oscillations of vehicles at nonlinear characteristics of the suspension
Keywords: транспортні засоби; математична модель коливань; нелінійні коливання; пружна підвіска; амплітуда; частота коливань